Natural capital depletion and sustainable development: evidence from Nigeria (2023)
This study is an empirical investigation into the relationship between sustainable development and natural capital depletion in Nigeria. The study uses time series data from 1990 to 2020 on adjusted net saving, including particulate emission damage as a percentage of Gross National Income (GNI) using Adjusted Net Saving (ANS) as a proxy variable for sustainable development, while natural capital depletion is proxied using total natural resources rents as a percentage of GDP for capturing Natural capital (NC). The gross national income per capita (GNI) and the inflation rate (INF) are considered control variables in the study. Adopting the Autoregressive Distributed Lag (ARDL) model and the Bounds test approach to cointegration, the study finds a long-run relationship among the variables. While the main independent variable, NC positively relates to ANS, the relationship is found to be statistically insignificant. GNI is found to negatively impact ANS while INF showed a mixed relationship with ANS across the short and long run. The study concludes that Nigeria must look beyond depleting the stock of natural resources for the purpose of driving sustainable development.